Clinical Operation Specifications for Walking Assistive with Functional Electrical Stimulation - YAN Tiebin; CHEN Hanbo; WU Wei; XUE Jingjing; HE Xiaokuo; SUN Qianqian; SUN Wenjing; ZHANG Shunxi; LI Chunzhen; WEI Xijun; ZHUANG Zhiqiang; WEI Ni; et al. (康复学报, 2025)
Functional electrical stimulation for gait assistance (FES-gait) represents a crucial rehabilitation technology for improving walking function in patients with central nervous system injuries. However, standardized operational protocols for clinical application are currently lacking. In order to standardize the clinical application of assisted FES and improve the therapeutic effect and safety, a project group led by experts from Sun Yat-sen Memorial Hospital of Sun Yat-sen University formulated the Clinical Operation Specifications for Walking Assistive with Functional Electrical Stimulation based on evidence-based medical evidence and clinical practice experience. According to the clinical operation process, this standard regulates the clinical application indications, evaluation before and after treatment, motion point detection, equipment preparation, environmental requirements, operation during treatment, treatment after treatment, and efficacy evaluation of FES. This standard can provide guidance for the systematic and standardized application of FES technology, improve the consistency and safety of therapeutic effect, and promote the standardized application and promotion of FES technology in the field of neurological rehabilitation.